2020
DOI: 10.1039/c9ra07648d
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the doping level of PEDOT:PSS film by treatment with hydrazine to improve the Seebeck coefficient

Abstract: This paper reported the modulation of the doping level of PEDOT:PSS with hydrazine to remarkably improve its Seebeck coefficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(66 citation statements)
references
References 58 publications
6
60
0
Order By: Relevance
“…The dedoped cPEDOT showed a p-p* electronic transition peak at 615 nm, an intensified polaron absorption band centered at 982 nm, and a weakened bipolaron band from 1360 to 2000 nm, which is consistent with the literature. 36,37 The aforementioned UV-Vis-NIR data confirm the formation of doped PEDOT, ePEDOT, after e-polymerization.…”
Section: Papermentioning
confidence: 65%
See 1 more Smart Citation
“…The dedoped cPEDOT showed a p-p* electronic transition peak at 615 nm, an intensified polaron absorption band centered at 982 nm, and a weakened bipolaron band from 1360 to 2000 nm, which is consistent with the literature. 36,37 The aforementioned UV-Vis-NIR data confirm the formation of doped PEDOT, ePEDOT, after e-polymerization.…”
Section: Papermentioning
confidence: 65%
“…The broad bands centered at 970 nm and from 1360 to 2000 nm are attributed to the polaron (radical cation) and bipolaron (dication) charge carriers, respectively. [35][36][37] Next, the as-prepared ePEDOT on the ITO substrate was dedoped by treatment with ethylenediamine.…”
Section: Papermentioning
confidence: 99%
“…The environmental stability of both N-PEDOT:PSS and [bmim]-[OTf]-N-PEDOT:PSS films is better or comparable to that of these reported in literatures (Table S3, ESI †). [38][39][40]45,73…”
Section: Stability Study Of Pedot:pss Filmsmentioning
confidence: 99%
“…35 In their recent work, they used ionic liquid to treat PEDOT:PSS films, and obtained an extremely high PF of 754 mW m À1 K À2 , 36 being much greater than that obtained by Saxena et al using a same ionic liquid (PF = 170 mW m À1 K À2 ). 37 Recently, we reported a series of work on post-treatment of PEDOT:PSS film using a combination of chemicals including a variety of reagents such as formamide, 8 formic acid, 38 trifluoroacetic acid, 19 trifluoromethanesulfonic acid, 24 hydrazine, 38 formaldehyde sulfoxylate 39 and ionic liquid. 40 For example, PEDOT:PSS films were post-treated with formamide and ionic liquids, and it was found that treatment only marginally had effect on the s but remarkably increased the S, achieving an overall PF up to B239.2 mW m À1 K À2 .…”
Section: Introductionmentioning
confidence: 99%
“…Another explanation for improved electrical conductivity is explained by a different mechanism in which the selective removal of nonconductive PSS over PEDOT is indicated by a change in the XPS peak ratio between PEDOT and PSS whereby more PEDOT is present at the surface of the film relative to a control (pristine PEDOT:PSS). 276,363 As shown in Figure 4.7.3 (a) the most notable significant peak intensity at (1440 cm -1 ) is shown to be produced by the propylene glycol. Although not normalized, it would be expected since all films were measured at the same time frame under the same settings for the intensity to be similarly matched unless a significant chemical change had occurred.…”
Section: Morphology Of Pedot:pss Thin Filmsmentioning
confidence: 92%